Application of Vibration Correlation Technique for Open Hole Cylinders - Skukis, Eduards; Kalnins, Kaspars; Ozolins, Olgerts (NTU "KhPI", 2016)
As non-destructive method for axial buckling load determination - Vibration Correlation Technique (VCT) showed major advantages for a range of industrial application. Particular technique for validation of structural limit state in accordance to numerical model prediction for large (true) scale structures are getting the required momentum. The Vibration Correlation Technique (VCT) allows to correlate the ultimate load or instability point with rapid decrement of self-frequency response. Nevertheless this technique is still under development for thin-walled shells and plates. The current research discusses an experimental verification of extended approach, applying vibration correlation technique, for the prediction of actual buckling loads on unstiffened isotropic cylindrical shells with circular cut-outs, loaded in axial compression. Validation study include several aluminium cylinders which were manufactured and repeatedly loaded up to instability point. In order to characterize a correlation with the applied load, several initial natural frequencies and mode shapes were measured during tests by 3D laser scanner. Results demonstrate that proposed vibration correlation technique allows one to predict the experimental buckling load with high reliability, by loading up to % of ultimate load. Additional experimental tests including geometric imperfections from initial manufacturing and postbuckling mode shape are currently under development to further validation ofproposed approach.
Keywords: vibration correlation technique; buckling; thin-walled structures; cylindrical shells